2020
DOI: 10.1186/s13054-019-2719-8
|View full text |Cite
|
Sign up to set email alerts
|

Should the ultrasound probe replace your stethoscope? A SICS-I sub-study comparing lung ultrasound and pulmonary auscultation in the critically ill

Abstract: Background: In critically ill patients, auscultation might be challenging as dorsal lung fields are difficult to reach in supine-positioned patients, and the environment is often noisy. In recent years, clinicians have started to consider lung ultrasound as a useful diagnostic tool for a variety of pulmonary pathologies, including pulmonary edema. The aim of this study was to compare lung ultrasound and pulmonary auscultation for detecting pulmonary edema in critically ill patients. Methods: This study was a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
2
27
0
2
Order By: Relevance
“…Ultrasound is considered to be the fifth pillar of physical examinations, 2 and there is an open debate on whether ultrasound should replace stethoscopes in certain scenarios. 3 This same scenario has been shown to happen in echocardiography, where medical students who have trained to recognize cardiovascular disease showed a greater accuracy in their diagnoses using pocket ultra-sounds than a trained cardiologist using a traditional physical examination. 4 We would like to strongly encourage the medical community to not rely solely on auscultation in patients with dyspnea, reduce their use of X-rays and do selective CT scans in this pandemic.…”
mentioning
confidence: 80%
“…Ultrasound is considered to be the fifth pillar of physical examinations, 2 and there is an open debate on whether ultrasound should replace stethoscopes in certain scenarios. 3 This same scenario has been shown to happen in echocardiography, where medical students who have trained to recognize cardiovascular disease showed a greater accuracy in their diagnoses using pocket ultra-sounds than a trained cardiologist using a traditional physical examination. 4 We would like to strongly encourage the medical community to not rely solely on auscultation in patients with dyspnea, reduce their use of X-rays and do selective CT scans in this pandemic.…”
mentioning
confidence: 80%
“…Several studies have demonstrated that LUS has comparable or superior accuracy compared with chest radiography for many of the most common causes of dyspnea. 3 However, few studies have compared LUS with pulmonary auscultation 4 in the follow-up of patients.…”
mentioning
confidence: 99%
“…Conventional physical examination has limited diagnostic utility to predict the fluid status and to guide vasoactive therapy in hemodynamically unstable patients [11]. Of particular note, the diagnostic accuracy of auscultation for detection of alveolar-pulmonary edema is only about 55-67% [12], which is likely to be even lower when using disposable stethoscopes in the noisy ICU environment. Adding to this, several of our clinical assumptions are either inaccurate or have limited value in the case of critically ill patients.…”
Section: What Is the Problem With "Conventional" Assessment?mentioning
confidence: 99%
“…POCUS is a bedside ultrasound examination performed by the clinician to answer focused question(s) and guide management. Studies have consistently confirmed that it can improve the diagnostic accuracy of physical examination in various clinical backdrops [12,16]. However, isolated use of lung or inferior vena cava (IVC) ultrasound is subject to limitations in this context.…”
Section: What Is the Problem With "Conventional" Assessment?mentioning
confidence: 99%